THE ROLE OF LOCAL GOVERNMENT IN DISASTER MANAGEMENT (Study on the Regional Disaster Management Agency in Flood Disaster Mitigation in Samarinda City) - Khaerani, Thalita (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
Flooding in Samarinda City is a problem that never ends every year. Based on Law Number 24 of 2007 concerning Disaster Management, the implementation of disaster management in situations of potential disaster includes: preparedness, early warning, and disaster mitigation. This study aims to analyze the stages of flood disaster mitigation in Samarinda City based on Law Number 24 of 2007 concerning Disaster Management. This type of research uses qualitative descriptive research with informant selection through purporsive techniques. Data collection techniques through observation, in-depth interviews, documentation and literature study and data analysis techniques using the triangulation method. The results showed that the efforts made by the BPBD of Samarinda City in disaster mitigation were mapping disaster-prone areas, monitoring in disaster-prone areas, socializing and disseminating information as well as coordinating with local governments and conducting education and training. The inhibiting factors in disaster mitigation are budget constraints, weak regulations, limited human resources in disaster management and low levels of public awareness. gb777